2020
DOI: 10.1093/pubmed/fdaa031
|View full text |Cite
|
Sign up to set email alerts
|

Retention of physicians and surgeons in rural areas—what works?

Abstract: Background Causes for health inequity among rural populations globally are multifactorial, and include poorer access to healthcare professionals. This study summarizes the recent literature identifying factors that influence rural doctor retention and analyses strategies implemented to increase retention. Uniquely, this study addresses the importance of context in the planning, implementation and success of these strategies, drawing on literature from high-, middle- and low-income countries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 34 publications
0
45
0
Order By: Relevance
“…One systematic review met eight out of 11 quality criteria (MacQueen et al 2018), with issues including a lack of clarity around how quality appraisal and publication bias assessment was conducted, and the absence of recommendations for future research. One systematic review met seven quality criteria (Kumar and Clancy 2020) due to unclear description of their search strategy, insufficient number of resources and databases searched, and lack of clarity on publication bias assessment. One systematic review met six quality criteria out of 11 due to insufficient risk of bias assessment, lack of clarity in data extraction methods, and the absence of clear recommendations for policy and practice and for future research (Suphanchaimat et al 2016).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One systematic review met eight out of 11 quality criteria (MacQueen et al 2018), with issues including a lack of clarity around how quality appraisal and publication bias assessment was conducted, and the absence of recommendations for future research. One systematic review met seven quality criteria (Kumar and Clancy 2020) due to unclear description of their search strategy, insufficient number of resources and databases searched, and lack of clarity on publication bias assessment. One systematic review met six quality criteria out of 11 due to insufficient risk of bias assessment, lack of clarity in data extraction methods, and the absence of clear recommendations for policy and practice and for future research (Suphanchaimat et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…However, Kumar and Clancy (2020) reported that for IMGs in HICs visa waiver programmes were identified as a non-effective retention strategy. The same review reported that compulsory rural service programmes for physicians were effective as a retention strategy in HICs but that the evidence was inconclusive within MICs (Kumar and Clancy 2020). One further systematic review reported that evidence base for financial incentives with RoS was mixed (Verma et al 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations